Porphyrin–nanodiamond hybrid materials—active, stable and reusable cyclohexene oxidation catalysts - Dias, Lucas D. (2020)
funded by FCT-Foundation for Science and Technology, I.P., under projects UIDB/00313/2020; PTDC/QUI-OUT/27996/2017 (DUALPI); POCI-01-0145-FEDER-027996; POCI-01-0145-FEDER-016387; UIDB/50006/2020 (Associate Laboratory for Green Chemistry-LAQV); MATIS (CENTRO-010145-FEDER-00014); Base Funding-UIDB/50020/2020 of the Associate Laboratory LSRE-LCM-funded by national funds through FCT/MCTES (PIDDAC); and 5625-DRI-DAAD-2020/21. SACC also acknowledges FCT Investigador FCT program (IF/01381/2013/CP1160/CT0007) and Scientific Employment Stimulus -Institutional Call (CEECINST/00102/2018). The authors also thank Fundacao de Amparo a Pesquisa do Estado de Sao Paulo (FAPESP) for CEPOF 2013/07276-1, and INCT "Basic Optics and Applied to Life Sciences" (FAPESP 2014/50857-8, CNPq 465360/2014-9). A.R.L. Caires acknowledges CAPES-PrInt funding program (grant number 88887.353061/2019-00 and 88881.311921/2018-01). J.G.B. thanks the Dutch Research Council (NWO) for funding as a part of the Open Technology Programme (project number 16361). L.D. Dias thanks FAPESP for the Post-doc grant 2019/13569-8. F.M.S.R. thanks FCT for the PhD grant (PD/BD/114340/2016).